A formação acadêmica na graduação em Enfermagem e o atendimento pré-hospitalar - Sousa, Wanessa Rezende (2015)
This present study aims to understand the perception of nurses and nursing students on academic training to act in urgent and emergency service, specifically in Pre- Hospital Care - APH. Considering the proposed objectives, we decided to conduct a descriptive study with a qualitative approach, adopting the ‘Case Study’ as the method. We developed a literature review that addressed the history of nursing education, the conceptual and regulatory frameworks on Pre-hospital Care, the formation of nursing professional and the stage’s role in this formation. The empirical study was carried out in Nursing Management of Mobile Emergency Care Service - SAMU the State Health Department – SES, in Cuiabá, MT and Faculty of Nursing at the Federal University of Mato Grosso - UFMT - Cuiabá campus. The research subjects were the nurses of SAMU and students of the 9th semester of nursing graduation of UFMT - Cuiabá campus. We used as data collection technique the following instruments: A semi-structured interview, which was intended to SAMU nurses, from a script containing sixteen (16) questions; Two questionnaires for students of graduation, applied in two (2) different times; the documentary analysis on the Curriculum Guidelines of the Nursing Course; Pedagogical projects of the UFMT Nursing Courses of 2010, Curriculum Structure of courses dated 1976, 1983, 1990, 1996 and 2010, in addition to the menus of the disciplines that have relation with the theme Urgency and Emergency. For data analysis, we used data coding technique proposed by Bogdan and Biklen (1994). This system seeks regularity and standards, as the repetition of answers, words or phrases identifies how the subjects think. In the documentary analysis, as regards the menus all approach broadly nursing assistance, not being possible to identify the deepening of the content to be covered in the case of APH. In general, nurses and nursing students indicate the deficiency in the teaching undergraduate in relation to emergency situations, the lack of preparation of students to enter the labor field, since this gap could be decreased giving opportunities to academic stage in emergency units and especially in pre-hospital care.